The Utilization of Digital Platforms in Islamic Religious Education Learning at SMA Negeri 1 Muaro Jambi - Chandra Kirana; Sururudin (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study examines the utilization of digital platforms in Islamic Religious Education (Pendidikan Agama Islam/PAI) learning at SMA Negeri 1 Muaro Jambi, Indonesia. Although PAI learning at this institution had begun incorporating digital platforms including Google Classroom, WhatsApp Group, and YouTube no systematic investigation had examined the processes, effectiveness, or mediating factors of this implementation. This study employed a qualitative approach with a descriptive case study design. Data were collected through passive participatory observation, semi-structured in-depth interviews with PAI teachers, students, and school administrators, and documentation analysis. Data analysis followed the interactive model of Miles and Huberman, while trustworthiness was established through source, technique, and time triangulation, as well as member checking. The findings reveal three principal outcomes: (1) digital platforms were implemented through a systematic three-stage framework planning, implementation, and evaluation utilizing a blended learning model that combined synchronous and asynchronous modalities; (2) the primary supporting factors included institutional commitment, teacher digital competence, and student motivation, whereas internet infrastructure inequality, variable digital literacy, and digital distraction constituted the principal inhibiting factors; and (3) digital platform utilization produced meaningful improvements across cognitive, affective, and psychomotor learning outcomes, with the most consistent gains observed in the cognitive domain. These findings suggest that effective digital PAI instruction requires a theoretically grounded balance between technological innovation and the preservation of PAI's irreplaceable spiritual and relational pedagogical dimensions.